The Youth for Technology Foundation: digital opportunities - Jain, Hemlata (Technical Centre for Agricultural and Rural Cooperation, 2004)
Hemlata Jain explains how the Owerri Digital Village is providing ICT training for disadvantaged youth in eastern Nigeria to help them develop their self-confidence and an entrepreneurial spirit.